Pastoral care and religious support as a part of treatment of religious patient with the severe form of osteoarthritis - Đurović, Aleksandar Gojko; Sovilj, Saša; Djokić, Ivana; Brdareski, Zorica; Vukomanović, Aleksandra; Ilić, Nataša; Milavić-Vujković, Merica (Vojnosanitetski pregled, 2017)
Introduction. Religious needs of patients are consistently being neglected in the clinical medicine. Pastoral care is a religious support which a religious patient receives from priests, chaplains, imams, rabbis or other religious authorities. Religious support, in terms of clinical medicine, is a spiritual support which religious patients obtain from religious and trained medical workers. The aim of this report was to present the effects of pastoral care and religious support in hospital treatment of a 73-year-old patient with the severe form of osteoarthritis. Case report. The 73-year-old, highly religious patient with severe form of osteoarthritis was admitted at the Clinic for Physical Medicine and Rehabilitation, Military Medical Academy in Belgrade, due to heterogeneous problems in the activities of daily living. The patient walked with difficulty using a stick, suffered pain, and was anxious and depressive. In order to objectively demonstrate effects of both pastoral care and religious support in this patient we performed multiple treatment with reversal design, in which the basic treatment consisting of hospital care, pharmacotherapy and physical therapy (the treatment A) was alternatively changed with the treatment that included combination of the basic treatment and religious support provided by religious physiatrist and physiotherapist (the treatment B) or combination of the basic treatment and pastoral care provided by military priest (the treatment C). The treatment A was applied three times and lasted two weeks, every time. Treatments B and C were applied once and lasted three weeks, each. The order of the treatments was: A→B→A→C→A. During the whole treatment period the patient’s condition was assessed by several measuring scale: the level of depression by The Hamilton Rang Scale for Depression and The Zung Self Rating Depression Scale; the level of anxiety by The Zung Self Rating Anxiety Scale; the functional capability of patient by The Barthel Index and The Functional Independent Measure. Measuring was carried out on a daily basis. In statistical analysis two nonparametric statistic were used: the percentage of non-overlapping data (PND) and the percentage of data points exceeding the median (PEM). PND and PEM values below 0.7 reflect questionable effectiveness of the treatment. The values between 0.7 and 0.9 reflect moderate effects. The values above 0.9 are considered as a highly effective treatment. The anxiety of the patient was moderately to significantly reduced after introducing religious support (treatment B: mean and mean deviation = 50.1 ± 10.89; variability = 4.598653; mean shift = 0.219626; PND = 0.6; PEM = 0.9) and pastoral care (treatment C: mean and mean deviation = 53.5 ± 5.90; variability = 9.062591; mean shift = 0.207407; PND = 0.9; PEM = 0.9). The patient’s depression was reduced after introducing pastoral care (treatment C: mean and mean deviation = 51.3 ± 4.66; variability = 10.99005; mean shift = 0.08881; PND = 0; PEM = 0.9). On the contrary, the patient’s functional capability was not significantly improved. Conclusion. In the highly religious patient with severe osteoarthritis pastoral care and religious support, applied along with the standard medical treatment of this condition, produced some beneficial effects on anxiety and depressive mood, but with no significant effect on patient’s functional capability.
Keywords: physical and rehabilitation medicine; osteoarthritis; religion; pastoral care; aged; treatment outcome